2019
DOI: 10.1111/zph.12558
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the prevalence of thermotolerant Campylobacter in food‐producing animals worldwide

Abstract: The objective of this meta-analysis was to summarize available information on the prevalence of thermotolerant Campylobacter (TC) in different food-producing animals worldwide. Databases (i.e., PubMed, ScienceDirect, Scopus) were searched from 1980 to 2017 unrestricted by language. The inclusion criteria were as follows: prevalence or incidence studies, published in peer-reviewed journals, and they must have reported the total number of animal samples studied and the number of samples that were positive for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Additional assays, such as PCR, improve the discrimination between Campylobacter strains ( Gharst et al., 2013 ). However, consistent with these findings, earlier research found that C. jejuni was more prevalent than C. coli in poultry samples ( Giombelli and Gloria, 2014 , Panzenhagen et al., 2016 , Casagrande Proietti et al., 2018 , Rossler et al., 2019 ). Note that in the present study, however, the majority of C. jejuni strains were isolated in Preston agar.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Additional assays, such as PCR, improve the discrimination between Campylobacter strains ( Gharst et al., 2013 ). However, consistent with these findings, earlier research found that C. jejuni was more prevalent than C. coli in poultry samples ( Giombelli and Gloria, 2014 , Panzenhagen et al., 2016 , Casagrande Proietti et al., 2018 , Rossler et al., 2019 ). Note that in the present study, however, the majority of C. jejuni strains were isolated in Preston agar.…”
Section: Resultssupporting
confidence: 73%
“…Campylobacteriosis is among the leading foodborne diseases reported worldwide ( Rossler et al., 2019 , Tack et al., 2019 ). Campylobacter jejuni accounts for most of the 90% of culture-confirmed human cases, whereas infection with Campylobacter coli and other related species occurs to a lesser extent ( Patrick et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found no evidence for increased pathogen prevalence in bird faeces on farms that integrated livestock. The extensified, small-scale livestock production on farms in our study might have decreased environmental runoff alongside decreased pathogen prevalence in the livestock compared to their counterparts in more intensified systems (Gerber, Chilonda, Franceschini, & Menzi, 2005;Rossler et al, 2019). Conversely, the large daily movements of many bird species, such as European starlings and native blackbirds (Gaulker, Homan, George, & Bleier, 2012;Heisterberg, Knittle, Bray, Mott, & Besser, 1984), may increase the importance of landscape-scale livestock intensification relative to on-farm livestock integration for pathogen prevalence dynamics because highly mobile organisms can acquire and disseminate pathogens across large distances.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, intensification of mammalian livestock production around farms might expose birds to more pathogens, thereby increasing food safety risks (Rossler et al, 2019).…”
Section: Discussionmentioning
confidence: 99%